Arthroscopic cartilage regeneration facilitating procedure: A decompressing arthroplasty for knee osteoarthritis. Issue 39 (30th September 2022) - Lyu, Shaw-Ruey; Hsu, Chia-Chen; Hung, Jung-Pin; Chou, Li-Chan; Chen, Yu-Ruei; Lin, Chih-Wen
Abstract : The effectiveness of arthroscopic treatment for knee osteoarthritis (OA) has always been a subject of debate. This study presents an innovative concept for the arthroscopic management of knee OA and investigates its clinical outcomes. An arthroscopic cartilage regeneration facilitating procedure (ACRFP) was performed on 693 knees of 411 patients with knee OA, with a mean age of 60 years (34–90 years), to eliminate the medial abrasion phenomenon (MAP) and decompress the patellofemoral joints. The Knee Society Score (KSS) and Knee Injury and Osteoarthritis Outcome Score (KOOS) were used to determine the subjective outcome. Roentgenographic changes in all cases and magnetic resonance imaging (MRI) variations in 20 randomly selected cases were evaluated for objective outcomes. We evaluated 634 knees in 369 patients (93.7%) with more than 3 years of follow-up (mean, 40 months; SD, 9) and found that the overall subjective satisfaction rate was 91.1%. Scores for KSS and all KOOS subscales improved statistically. Reversal of cartilage degeneration was observed in 80.1% of the entire series (radiographic outcome study) and 72.2% of the 18 randomly selected cases (1-year MRI outcome study). We found significant association between gender and OA severity, with regards to the subjective outcomes. Age, body mass index, pre-operative hyaluronic acid injection, OA severity, and type and severity of the medial plica were found to be important predictors of radiographic outcomes. An analysis of failed cases reaffirmed the need for early ACRFP and skilled post-operative care. ACRFP is an effective treatment for knee OA. It can benefit most patients and modify their degeneration processes if performed in time. However, further investigations are needed to confirm our concept of treatment.